Maternal and infant bonding: Concept Paper - Kufakunesu, Lilian; Kasu, Christine Mary; Mugadza, Gladys (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2017)
Maternal-infant bonding is a maternal-driven process that occurs primarily throughout the first year of a baby’s life, but may continue throughout a child’s life. It is an affective state of the mother; maternal feelings and emotions toward the infant are the primary indicator of maternalinfant bonding. The first hour of life is very critical in any baby’s life and it is the critical hour to create a bond between a mother and her baby. Objective: The purpose of the concept analysis was to describe the importance, barriers and consequences of Maternal-infant bonding. Methods and materials Walker and Avant model of concept analysis which looks into the attributes, antecedence and consequences, exemplars and recommendations was used. Literature search was conducted in a month’s and a half’s time using, bonding journals, Pub- med and MEDLINE, Google and Google Scholar as search engines. Twenty four studies that were found relevant to the concept of interest were included in the description of maternal and infant bonding. Maternal and infant bonding was encouraged in most of the studies. Results It was noted that preconception care plays a vital role in the bonding process as pre conception women can learn how to bond with their babies even when they are pregnant and not to wait for the baby to be born. Conclusion and recommendations Midwives and all other health professionals are encouraged to include maternal and infant bonding in most of the health education sessions.